2017
DOI: 10.1038/cddis.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex I inhibition triggers a mitophagy-dependent ROS increase leading to necroptosis and ferroptosis in melanoma cells

Abstract: Inhibition of complex I (CI) of the mitochondrial respiratory chain by BAY 87-2243 ('BAY') triggers death of BRAF V600E melanoma cell lines and inhibits in vivo tumor growth. Here we studied the mechanism by which this inhibition induces melanoma cell death. BAY treatment depolarized the mitochondrial membrane potential (Δψ), increased cellular ROS levels, stimulated lipid peroxidation and reduced glutathione levels. These effects were paralleled by increased opening of the mitochondrial permeability transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
274
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(307 citation statements)
references
References 73 publications
5
274
3
Order By: Relevance
“…TRAP1, along with HSP90 mitochondrial pool and HSP60, has been described to physically interact with matrix CypD modulating its regulatory activity and resulting in mPTP inhibition . Surprisingly, TRAP1 depletion resulted in a more closed mPTP conformation under basal conditions, which was the opposite effect to that observed in melanoma . Our result was not due to loss of CypD expression or activity as CypD expression was intact and addition of cyclosporin A resulted in an increase in mPTP closing.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…TRAP1, along with HSP90 mitochondrial pool and HSP60, has been described to physically interact with matrix CypD modulating its regulatory activity and resulting in mPTP inhibition . Surprisingly, TRAP1 depletion resulted in a more closed mPTP conformation under basal conditions, which was the opposite effect to that observed in melanoma . Our result was not due to loss of CypD expression or activity as CypD expression was intact and addition of cyclosporin A resulted in an increase in mPTP closing.…”
Section: Discussioncontrasting
confidence: 51%
“…3,8 Surprisingly, TRAP1 depletion resulted in a more closed mPTP conformation under basal conditions, which was the opposite effect to that observed in melanoma. 38 Our result was not due to loss of CypD expression or activity as CypD expression was intact and addition of cyclosporin A resulted in an increase in mPTP closing. The discrepancy with previous works may reflect that these studies relied on extrapolation of mPTP status from analysis of DΨ m alterations 8 or on evaluation of cell viability in the presence or absence of CsA.…”
Section: Discussionmentioning
confidence: 57%
“…Elevated ROS values can induce mitophagy . To investigate whether PQS treatment would modulate the degree of mitophagy in HeLa cells, the distribution of the fusion protein LC3::mCherry after PQS treatment was compared with the control.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated ROS values can induce mitophagy. 46 To investigate whether PQS treatment would modulate the degree of mitophagy in HeLa cells, the distribution of the fusion protein LC3::mCherry after PQS treatment was compared with the control. During the activation of autophagy pathways, 22 amino acids are cleaved from the C-terminus of LC3 to form LC3-II which selectively localizes in newly formed autophagosomes.…”
Section: Pqs Treatment Does Not Stimulate Mitophagymentioning
confidence: 99%
“…[37] Schockel et al recently demonstrated that BAY 87–2243, a potent inhibitor of NADH-coenzyme Q oxidoreductase (complex I), induced dose-dependent ferroptosis on a panel of BRaf V600E melanoma cell lines. [38,39] Summarily, the experimental compounds including erastin, 1,2-dioxolane, siramesine, lapatinib, and BAY 87–2243 (Figure 1), are promising as potential clinical drugs for ferroptosis-based cancer therapy.…”
Section: Small Molecules For Ferroptosis-based Cancer Therapymentioning
confidence: 99%